Assédio moral em instituições de ensino superior(IES): o caso dos servidores técnico-administrativos da Universidade Federal do Ceará (UFC) - Damasceno, Thalita Natasha Ferreira (2012)
The moral harassment at work is characterized by embarrassing and hostile attitudes continually undertaken, which aims to harm the psychic dignity of the individual, and thus debasing the working environment. This phenomenon is of great importance in the labor relations context and involves the society as a whole. However, it is a topic still under construction. Meanwhile, this paper aims to contribute to reducing the lack of studies in this area, through a survey that aims to: describe mobbing and determine the factors which lead to the perception of harassment; to propose an assortment of moral harassment that takes into account the intent of the harasser and the harm to the victim‟s health; to organize a concept of mobbing from the federal employees‟ perspective; and, finally, to propose improvements in the workplace, with emphasis on psychological harassment. The methodology applied was a qualitative survey using the Delphi method of analysis, from a study of 40 (forty) workers of the Federal University of Ceará (UFC). From a concept organized with the convergence of the employees‟ replies, we realized that they have a consistent understanding of moral harassment. They understand the essence of the phenomenon, namely, the completion and repetition of the abusive and embarrassing act; they also have acute perception regarding the causes, consequences, prevention and combating harassment. However, they still have some gaps in perception regarding the attributes of the victim. Indeed, we wish that these results contribute to the better understanding and characterization about the mobbing at work, to assist the concerned people in effectively combating this organizational problem and be groundwork for forthcoming researches.